E3 ligase FBXW7 is critical for RIG-I stabilization during antiviral responses - Yinjing Song (Nature Portfolio, 2017)
The innate immune response to many RNA viruses depends on recognition of viral RNA by RIG-I. Here the authors show that, upon virus infection, FBXW7 interacts with RIG-I and inhibits ubiquitin-mediated degradation of RIG-I, resulting in increased interferon signallingin vitro and in vivo.